PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN CALON PENERIMAAN BEASISWA PADA SMK NEGERI 12 BERBASIS WEBSITE DENGAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) - Dhienny Aviya Miro, (2021)
In today's life, education is one of the most important needs, the state is very supportive for every citizen to achieve the highest education. But behind it all, there are many people who cannot afford the highest education. Therefore, the government implements a scholarship program for its citizens who feel less well off. The purpose of this study is to help the school of SMK Negeri 12 North Jakarta in selecting prospective students who will receive scholarships in the school environment, and it is hoped that this system is able to determine the best alternative based on the characteristics of each performance. The results in this study are a decision support application system that can help the school to determine which students will get scholarships according to existing criteria.